2006
DOI: 10.1016/j.jacc.2006.04.082
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Transplant Coronary Artery Disease Using Multidetector Computed Tomography With Adaptative Multisegment Reconstruction

Abstract: Detection of occlusive coronary disease in heart transplant recipients with elevated resting heart rate by MDCT is feasible using multicycle reconstruction. The need for surveillance invasive coronary angiography in transplant recipients might be mitigated by use of MDCT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
44
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 27 publications
0
44
0
Order By: Relevance
“…In agreement with this, MDCT with adaptive multisegment reconstruction has a sensitivity and specificity of 86% and 99%, respectively. 70 In addition, 64-slice MDCT provides good to excellent image quality and has moderate to excellent test characteristics for the detection of CAV. 41 Iyengar et al 71 found a good overall agreement of conventional catheter-based angiography and 64-slice MDCT, with MDCT eventually being superior to identify nonobstructive vessel wall disease.…”
Section: Multidetector Ctmentioning
confidence: 99%
“…In agreement with this, MDCT with adaptive multisegment reconstruction has a sensitivity and specificity of 86% and 99%, respectively. 70 In addition, 64-slice MDCT provides good to excellent image quality and has moderate to excellent test characteristics for the detection of CAV. 41 Iyengar et al 71 found a good overall agreement of conventional catheter-based angiography and 64-slice MDCT, with MDCT eventually being superior to identify nonobstructive vessel wall disease.…”
Section: Multidetector Ctmentioning
confidence: 99%
“…The literature provides some data regarding the heart transplant population: Sigurdsson et al [93] used a 16-detector MDCT to identify coronary stenosis and compared to angiographic disease (defined by luminal stenosis > 95%). Sensitivity, specificity, positive and negative predictive values were 86%, 99%, 81% and 99% respectively, unfortunately only a few subgroup of patients underwent IVUS.…”
Section: Multidetector Computed Tomographymentioning
confidence: 99%
“…Among the different non-invasive imaging techniques routinely employed in the diagnostic work-up of cardiac allograft vasculopathy, i.e. nuclear perfusion tests [3] and stress echocardiography [4], multidetector computed tomography (CT) has emerged as a promising tool to reliably rule out this disease [5][6][7][8]. In particular, dual-source CT (DSCT) has been shown to provide diagnostic image quality in heart transplant recipients [9] while allowing significant coronary allograft vasculopathy to be reliably excluded [10].…”
Section: Introductionmentioning
confidence: 99%